An SFDI observer-based scheme for a general aviation aircraft - Ariola, Marco; Mattei, Massimiliano; Notaro, Immacolata; Corraro, Federico; Sollazzo, Adolfo (Zielona Góra: Uniwersytet Zielonogórski)
The problem of detecting and isolating sensor faults (sensor fault detection and isolation-SFDI) on a general aviation aircraft, in the presence of external disturbances, is considered. The proposed approach consists of an extended Kalman observer applied to an augmented aircraft plant, where some integrators are added to the output variables subject to faults.
Keywords: model-based FDI; sensor FDI; extended Kalman filtering; analytical redundancy; flight control